ANALYSING DIFFERENT PROMPTS FOR CHATGPT IN DEVELOPING WRITING SKILLS - Lee, Esther; Ganapathy, Malini (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Writing has consistently been a challenge for students, particularly when compared to other language skills. Among the four core competencies—listening, speaking, reading, and writing—students often struggle the most with writing. To enhance their writing proficiency, learners require high-quality model texts that demonstrate appropriate essay structure and linguistic features. ChatGPT has emerged as a valuable tool in this regard, offering substantial support in various fields, including EFL education. The model has demonstrated its ability to generate well-structured essays that serve as model texts, particularly in terms of grammatical accuracy, coherence and cohesion, and lexical resource—all essential components of effective academic writing. However, the quality of ChatGPT-generated content is highly dependent on the prompts used. This study aims to analyze the linguistic structures produced in response to different prompt types: open-ended, closed-ended, role-based, and iterative prompts. The findings indicate that open-ended and closed-ended prompts did not yield significant differences in linguistic structure, and both types exhibited areas for improvement. Overall, the essays generated from these prompts were assessed at a B2 level, suggesting that additional refinement—particularly through iterative prompting—would be necessary to produce outputs at the C2 level. Notably, role-based prompts provided references to support arguments; however, while these references were real, some of the information generated was fabricated. This highlights a critical limitation of ChatGPT: the potential for misinformation, necessitating careful verification of its outputs. Furthermore, all three prompt types—open-ended, closed-ended, and role-based—produced responses in bullet-point format rather than fully developed argumentative essays, reinforcing the need for iterative prompting to refine and structure the content appropriately. Overall, ChatGPT-generated essays serve as useful samples for learners seeking to improve their writing skills. However, to achieve more nuanced and expert-level guidance, instructor intervention remains essential.